(untitled) (Research, Society and Development, 2022)
This article covers considerations, and points out the determining milestones, which are linked to the history of Inclusive Education and Multifunctional Resource Rooms. In 2007, the Federal Government instituted the “Program for the ImplemeBntation of Multifunctional Resource Rooms” throughout Brazil, the result of years of efforts in favor of the inclusion of students with special educational needs in regular education, the struggle for equality for all and the effort to have a quality education for this public. Thus, this article aimed to understand the challenges of implementing the Multifunctional Resource Room and its contributions to children’s cognitive development. For this research, a qualitative bibliographic narrative review was used as a methodological procedure, based on publications made in the last ten years (2012 - 2022) of scientific articles, magazines, books, theses, dissertations and legislation, by different authors that deal with the topic. under investigation in order to structure a theoretical framework. In view of these findings, it is concluded that this work achieved the objectives presented, since it was inferred that the Specialized Educational Service and especially the Resource Room are fundamental elements for Inclusive Education. It is possible to say that the Multifunctional Resource Room is relevant for the activities of the Specialized Educational Service to be satisfactory, as it provides specific and individualized stimuli for the evolution of an intellectual and motor development of students with special educational needs.